Efecto de cuatro concentraciones de microorganismos eficientes (EM), aplicados a pulgones y queresas en naranjo (citrus sinensis) en el Bajo Mayo - San Martín - Isla Ramirez, Edward (2005)
This report is the result of research work in the field of "The Union" district of La Shilcayo between the months of June 2003 to February 2004 research. Aimed to evaluate the effects of four concentrations of Efficient Microorganisms EM (Efficient Microorganisms), in the town of homópteros (maggots and aphids) in orange (Citrus sinensis), in the valley on May in the region of San Martin, a goal that was achieved and whose approach was determined by the high incidence of pests in the citrus activity in the region, specifically the homopterous order. The research design used was the challenge of DBCA randomized complete block with four replicates per treatment. The treatments used were four, each treatment contenla a given concentration of EM effective microorganisms; for treatment 1 (T1) 0,50%, for treatment 2 (T2) 1,00%, for treatment 3 (T3) 1.50%, and for treatment 4 (T4) 2.00% addition an absolute control (tO) evaluations were fortnightly prior to the evaluations carried out after application, an initial evaluation before application of treatments performed, in order to see the degree of initial infestation population. Having done the statistical analysis and the respective interpellation of the results of evaluations, he reached the following conclusions; The greatest effect "biocide" EM was observed in citrus leaves and branches, where a negative correlation between the population incidence and concentration of E M. Treatment with 1.5% concentration of MS had exercised great control leaves and branches with 1.00 average infestation for both degrees. a clear effect of treatments on fruits was observed, possibly due to a heterogeneous planting, Valencia orange varieties, Washington navel, mandarin and common orange tree had , resulting in a variation in the process of fructification attack aphid is limited to the period of sprouting, ie the months of December. - January to June -. Julio (table No. 2) climate factor that has greater applying correlation for the treatment of MS is Homoptera precipitation. It is from these findings that raised the following recommendations: Repeat the experiment using higher concentration of M.S. and homogeneous plantations (of the same variety). Make observations in different sectors, where rainfall is low and the incidence of homopteran is greater. Make observations in longer period of time, to establish a correlation seasonal effect on the population of homópteros, should test the effect of effective microorganisms (M.S.) in laboratory conditions. Make phenological observations, by variety to establish critical periods. In addition, he contributed to our contribution in the process of initial research on pest control with efficient in the region microorganisms, but I think it is still incipient, we need a greater number of experiments, such as outlined in the recommendations given in this work to reach conclusions more successful and from it to pose a pest management program with this product.